2021
DOI: 10.1148/ryai.2021200172
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Semiquantitative Analysis of Cardiomegaly, Pneumothorax, and Pleural Effusion on Chest Radiographs

Abstract: To develop and evaluate deep learning models for the detection and semiquantitative analysis of cardiomegaly, pneumothorax, and pleural effusion on chest radiographs. Materials and Methods:In this retrospective study, models were trained for lesion detection or for lung segmentation. The first dataset for lesion detection consisted of 2838 chest radiographs from 2638 patients (obtained between November 2018 and January 2020) containing findings positive for cardiomegaly, pneumothorax, and pleural effusion that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Such improvement in detection of findings with AI has been reported in several prior studies . Prior studies with our AI as well as other research and commercial AI algorithms have reported comparable or lower diagnostic performance for detection of pneumothorax, pleural effusion, pneumonia, and pulmonary nodules. Although the stand-alone performance of our AI algorithm was comparable to that of the radiologists and trainees in terms of sensitivity, it had substantially lower specificity.…”
Section: Discussionsupporting
confidence: 81%
“…Such improvement in detection of findings with AI has been reported in several prior studies . Prior studies with our AI as well as other research and commercial AI algorithms have reported comparable or lower diagnostic performance for detection of pneumothorax, pleural effusion, pneumonia, and pulmonary nodules. Although the stand-alone performance of our AI algorithm was comparable to that of the radiologists and trainees in terms of sensitivity, it had substantially lower specificity.…”
Section: Discussionsupporting
confidence: 81%
“…Then, the CTR can be calculated accordingly by traditional methods. Similar methods have been shown to be accurate and effective [ 12 , 13 , 14 , 15 , 16 ] in previous works. However, hemodialysis patients are predisposed to a considerable prevalence of pulmonary complications (e.g., pulmonary edema 8.20–20.50%, pleural effusions 22.95–33.80%) [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 69%
“…The performance of the technique was validated in the 2015 International Symposium on Biomedical Imaging Cell-Tracking Challenge [ 18 ]. However, we did not re-evaluate the model because many studies have tested the method [ 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%